Use of antenatal corticosteroids for preterm birth in Latin America: Providers knowledge, attitudes and practices - Aleman, Alicia (2013)
Background: Antenatal corticosteroids administered to women at risk of preterm birth is an intervention which has been proved to reduce the risk of respiratory distress syndrome, intraventricular hemorrhage, and neonatal mortality. There is a significant gap in the literature regarding the prevalence of the use of antenatal corticosteroids in Latin American countries and the attitudes and opinions of providers regarding this practice. The aim of this study was to assess the knowledge, attitudes and practices of health care providers regarding the use of antenatal corticosteroids in women at risk of preterm birth in Latin America. Methods: This was a multicenter, prospective, descriptive study conducted in maternity hospitals in Ecuador, El Salvador, Mexico and Uruguay. Physicians and midwives who provide prenatal care or intrapartum care for women delivering in the selected hospitals were approached using a self-administered questionnaire. Descriptive statistics was used. Results: The percentage of use of ACT in threatened preterm labour (TPL) reported by providers varies from 70% in Mexico to 97% in Ecuador. However, 60% to 20% of the providers mentioned that they would not use this medication in women at risk and would limit its use when there was a threatened preterm labour. In only one country recommended regimens of antenatal corticosteroids are followed by around 90% of providers whereas in the other three countries recommended regimens are followed by only 21%, 61%, 69% of providers. Around 40% of providers mentioned that they would administer a new dose of corticosteroids again, regardless the patient already receiving an entire regimen. Between 11% and 35% of providers, according to the countries, mentioned that they do not have adequate information on the correct use of this medication. Conclusions: This study shows that the use of this intervention could be improved by increasing the knowledge of Latin American providers on its indications, benefits, and regimens.